A filiação divina em Gálatas (4,1-7) e a filiação socioafetiva no direito de família brasileiro - Silva, Lusvaldo de Paula e (2023)
This dissertation aimed, first, to analyze the pericope that deals with the advent of divine filiation, in the Epistle to the Galatians (4,1-7). The purpose was to understand above all what would be the most appropriate interpretations for the apostle Paul's statement about the "fullness of time" having arrived. According to him, when this happened, the path was open to the "younger" children to become "greater" and then choose freedom instead of slavery, the Master instead of the "pedagogue". By fulfilling this script, they would receive "filial adoption", equally becoming "heirs". In the second chapter, attention was focused on understanding the maturation process of Brazilian society at the end of the 20th century, in the family and social aspect, and which led to the official recognition of socio-affective affiliation in family law, in contrast to the biological and patrimonial concerns at the beginning of that phase and which marked the legitimate affiliation. Based on what was discovered in these two moments, the next challenge was to investigate to what extent it would be possible to correlate the meaning of the statement about having reached ¿the fullness of time¿, in two filiations. The hypothesis envisioned was that they presented aspects that seemed to go together and that complemented each other: the passage of time and the spiritualization of being, composing a "background" that accompanies the saga of man throughout the course of his existence and that is responsible for bringing the lights of progress, material and spiritual. The end of the research achieved the general objective by demonstrating that it is indeed possible to make the correspondence, which appears to be complete. It clarified that the two events did not occur at a random or fortuitous moment in history, but rather at one where most people had open and mature minds to question and change the reality around them. Likewise, the specific objectives were achieved by highlighting that inner maturity is what is behind overcoming the period under the "pedagogue" and receiving the Master and his liberating message; which made it possible to open space in the family and in the social environment for the formal reception of affectionate children, protected against any and all discrimination. Finally, to analyze the initial chapter and pertinent to divine filiation, the historical-critical method was used, while the dissertation as a whole was based on bibliographical research, in which it sought to privilege those studies that are not content with examining the great complexity and depth of life through monochromatic lenses